Oxygen distribution in tumors: A qualitative analysis and modeling study providing a novel Monte Carlo approach. Issue 9 (12th August 2014) - Lagerlöf, Jakob H.; Kindblom, Jon; Bernhardt, Peter
Abstract : Purpose: : To construct a Monte Carlo (MC)‐based simulation model for analyzing the dependence of tumor oxygen distribution on different variables related to tumor vasculature [blood velocity, vessel‐to‐vessel proximity (vessel proximity), and inflowing oxygen partial pressure (pO2 )]. Methods: : A voxel‐based tissue model containing parallel capillaries with square cross‐sections (sides of 10 μm) was constructed. Greenˈs function was used for diffusion calculations and Michaelis‐Mentenˈs kinetics to manage oxygen consumption. The model was tuned to approximately reproduce the oxygenational status of a renal carcinoma; the depth oxygenation curves (DOC) were fitted with an analytical expression to facilitate rapid MC simulations of tumor oxygen distribution. DOCs were simulated with three variables at three settings each (blood velocity, vessel proximity, and inflowing pO2 ), which resulted in 27 combinations of conditions. To create a model that simulated variable oxygen distributions, the oxygen tension at a specific point was randomly sampled with trilinear interpolation in the dataset from the first simulation. Six correlations between blood velocity, vessel proximity, and inflowing pO2 were hypothesized. Variable models with correlated parameters were compared to each other and to a nonvariable, DOC‐based model to evaluate the differences in simulated oxygen distributions and tumor radiosensitivities for different tumor sizes. Results: : For tumors with radii ranging from 5 to 30 mm, the nonvariable DOC model tended to generate normal or log‐normal oxygen distributions, with a cut‐off at zero. The pO2 distributions simulated with the six‐variable DOC models were quite different from the distributions generated with the nonvariable DOC model; in the former case the variable models simulated oxygen distributions that were more similar to in vivo results found in the literature. For larger tumors, the oxygen distributions became truncated in the lower end, due to anoxia, but smaller tumors showed undisturbed oxygen distributions. The six different models with correlated parameters generated three classes of oxygen distributions. The first was a hypothetical, negative covariance between vessel proximity and pO2 (VPO‐C scenario); the second was a hypothetical positive covariance between vessel proximity and pO2 (VPO+C scenario); and the third was the hypothesis of no correlation between vessel proximity and pO2 (UP scenario). The VPO‐C scenario produced a distinctly different oxygen distribution than the two other scenarios. The shape of the VPO‐C scenario was similar to that of the nonvariable DOC model, and the larger the tumor, the greater the similarity between the two models. For all simulations, the mean oxygen tension decreased and the hypoxic fraction increased with tumor size. The absorbed dose required for definitive tumor control was highest for the VPO+C scenario, followed by the UP and VPO‐C scenarios. Conclusions: : A novel MC algorithm was presented which simulated oxygen distributions and radiation response for various biological parameter values. The analysis showed that the VPO‐C scenario generated a clearly different oxygen distribution from the VPO+C scenario; the former exhibited a lower hypoxic fraction and higher radiosensitivity. In future studies, this modeling approach might be valuable for qualitative analyses of factors that affect oxygen distribution as well as analyses of specific experimental and clinical situations.